Thomas O. Haakenson. Grotesque Visions: The Science of Berlin Dada. Bloomsbury, 2021. - Kathryn Holihan (Studies in 20th & 21st Century Literature, 2024)
Review of Thomas O. Haakenson. Grotesque Visions: The Science of Berlin Dada. Bloomsbury, 2021. 219 pp.
Keywords: grotesque; avant garde; vision; objectivity; empirical science